Distribution, Half Life Time and Placental Transfer of the Protease Inhibitor Trasylol - Beller, F. K; Epstein, M. D; Kaller, H (Thrombosis and Haemostasis, 1966)
A method is described for an assay of Trasylol in the circulation. By this method it was found that Trasylol disappears rapidly from the circulation. The half life time of elimination is approximately 150 minutes. The placental barrier is not crossed by this substance.